Myth and the ready-made in David Levinthal's toy stories. (17th July 2012) - Stracey, Frances
The rise, in the 1980s, of what is now labelled appropriation-photography can be understood as the full absorption of the logic of the ready-made into photographic art. Like its Duchampian predecessor, the deployment of the ready-made was used to question the nature of institutionalized art-photography: was art inherent to the photo's medium; was it an auratic attribute of the author; conferred by the institution; or ratified by its consumption? It also enabled a critique of the politics of representation at stake in photographic practice outside of the immediate institutions of art. However, the correlation of appropriation-photography and a politics of representation relies upon the reduced logic of the subversive effect of a re-presented image. David Levinthal's photographs of mass-produced toys extends the reduced logic of the ready-made cultural artefact through their playful configuration, as well as through the more complex forms of photographic technique this allows (such as magnification, blurring, depth of focus). This enables a distinctive critical re-presentation of cultural myth. However, Levinthal also introduces a number of photographic techniques, which would seem to renege on the avant-garde claims of appropriation-photography, such as the reintroduction of pictorial composition and the use of large-scale Polaroids that emphatically reassert the unique and the expertly crafted image. This article examines this ambiguity in Levinthal's work, particularly with respect to its presentation of myth, and diagnoses it as symptomatic of the conditions of recent art-photography.